DAMPAK SIGNIFIKAN PENAMBAHAN FONEM ‘-NG’ PADA LIRIK LAGU CELENG GULING; WIDI-WIDIANA TERHADAP MAKNA - I Gede Dwi Setiadi (Universitas Warmadewa, 2023)
This research is a form of semantic research but by modifying the phonological elements in it. It is well known that minor and fundamental changes in the syntactic structure will affect its meaning. This study uses qualitative methods and experimental methods. Qualitative methods intend to understand phenomena about what is experienced by research subjects such as perceptions, motivations, actions, and others holistically, by means of descriptions in the form of language words. In this case, a qualitative method is applied in analyzing the research data, namely the song Celeng Guling by Widi-Widiana. Then the experimental method is a method to find out the consequences of the treatment given to a thing being studied. The application in this case is by modifying the phoneme of a word in the lyrics of the song so that it produces different words and changes the structure of meaning in it. Keywords: Phoneme, Semantic, Structural, Balinese Song